Seismic monitoring of CO2 geosequestration using multi-well 4D DAS VSP: Stage 3 of the CO2CRC Otway project. (September 2022) - Yurikov, Alexey; Tertyshnikov, Konstantin; Yavuz, Sinem; Shashkin, Pavel; Isaenkov, Roman; Sidenko, Evgenii; Glubokovskikh, Stanislav; Barraclough, Paul; Pevzner, Roman
Highlights: Multi-well 4D DAS VSP tracks the evolution of CO2 injected at 1.5 km depth. The seismic data from five wells provide broadly consistent images of the plume with some differences due to different illumination of the target horizon, lateral variation of velocities, and seismic anisotropy. The 4D DAS VSP monitoring reveals that the injected CO2 merges with a previous CO2 plume in the same formation and remobilises it. This demonstrates that fibre-optic DAS receivers permanently installed in the subsurface have a potential for monitoring injection of gas into gas-saturated reservoirs. Abstract: An important part of any CO2 geosequestration project is to ensure CO2 containment and conformance in the subsurface. This is generally done by implementing a comprehensive, risk-based Measurement, Monitoring and Verification plan, a key element of which is active time-lapse seismic monitoring. However, high cost and environmental impact of the standard surface seismic monitoring dictate the need for a cost-effective and environmentally friendly alternative. An opportunity to develop such method emerges with advances in distributed acoustic sensing (DAS) technology, which turns an optical fibre into a seismic sensor with dense spatial sampling. DAS can be permanently deployed in multiple wells across the geosequestration site providing a robust and non-intrusive network of seismic receivers. This approach was developed and tested in the CO2CRC Otway project, where injection of 15 kt of CO2 at 1.5 km depth was monitored with a 4D vertical seismic profiling (VSP) using five borehole DAS arrays and mobile vibroseis sources. The 4D DAS VSP in each of the five wells provides broadly consistent images of the CO2 plume with some differences due to different illumination of the target horizon, lateral variation of velocities, and seismic anisotropy. When the newly injected CO2 reaches a CO2 plume created as a result of an earlier injection into the same formation ∼600 m updip, 4D DAS VSP shows a change in reflectivity in that area and beyond. This shows a potential of 4D DAS VSP for monitoring gas injection into gas-saturated reservoirs.